Examination of teacher mediation and its impact on foundational reading skills in Grade-R classrooms in Namibia - Nzwala, Kenneth (Rhodes University, Faculty of Education, Department of Education, 2019)
Grounded in the Sociocultural Theory (SCT) of Lev Vygotsky, this study examined teacher mediation and its impact on development of foundational reading skills in six Grade-R classrooms in the Zambezi Region of Namibia. It was a multiple case study with a mixed methods approach. Six Grade R classes attached to primary schools were studied to facilitate following of the same learners to Grade One. A purposive sampling technique was used to draw a sample of six Grade-R and Grade-One teachers. Learners were selected using stratified random sampling. Data were collected by means of interviews, observation of Grade R lessons, and an emergent Early Grade Reading Assessment (eEGRA) test. eEGRA facilitated benchmarking teacher efficacy in mediating Grade R learners' foundational reading skills. Nine Grade One learners per teacher per school took part in the test at the beginning of Grade One. Three 35-minute lessons, per Grade-R teacher, were observed. Data were analysed statistically using ANOVA with thematic qualitative analysis of interview data against document analysis of curricula, teacher planning and learner exercise books. The study established that teachers had no understanding of 'emergent literacy', did not promote a love of books, or promote learning through play. There was evidence of a language barrier during lessons, which potentially reduced the efficacy of teacher mediation. The curriculum was found to be inappropriate as it lacked guidance relevant to Grade R teachers. This point was particularly pertinent as all teachers in this study had not received Grade-R training and were therefore looking to the curriculum for support. The difference between what teachers said and what they did was revealed in their classroom practice. Lesson planning was found to be superficial and non-reflective, with a marked discrepancy between what was planned and what was done. The style of pedagogy was primarily transmissive and authoritarian. Finally, the socio-economic distribution of the schools did not demonstrate significant impact on learner performance in the benchmark test. This study concludes that the Grade-R curriculum needs to be revised to be culturally and age appropriate. Teachers should be trained to understand the speciality of Grade R, and support should be given to current teachers to adopt a child-centred, play-based approach to pedagogy.
Keywords: Reading (Elementary) -- Namibia -- Case studies; Elementary school teachers -- Namibia -- Case studies; Early childhood education -- Curricula -- Namibia; VygotskiiÌ†, L. S. (Lev Semenovich), 1896-1934